2007
DOI: 10.1055/s-2007-964883
|View full text |Cite
|
Sign up to set email alerts
|

Synopsis of the CASIROZ Case Study: Carbon Sink Strength of Fagus sylvatica L. in a Changing Environment ‐ Experimental Risk Assessment of Mitigation by Chronic Ozone Impact

Abstract: Databases are needed for the ozone (O(3)) risk assessment on adult forest trees under stand conditions, as mostly juvenile trees have been studied in chamber experiments. A synopsis is presented here from an integrated case study which was conducted on adult FAGUS SYLVATICA trees at a Central-European forest site. Employed was a novel free-air canopy O(3) fumigation methodology which ensured a whole-plant assessment of O(3) sensitivity of the about 30 m tall and 60 years old trees, comparing responses to an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 151 publications
(236 reference statements)
4
69
1
5
Order By: Relevance
“…Whereas the observed effects on Ponderosa pine and other conifers in California were associated with peak ozone concentrations that exceeded 200 nl l -1 (ppbv) (Miller and McBride, 1998), more recent studies have emphasised the overall increase in ozone concentrations outside major 'episodes', and the potential for chronic injury (Coyle et al, 2003). There have been successful experiments that have moved from the study of young trees (seedlings or saplings) in the laboratory to the field-scale fumigation of adult trees with ozone, recognising that the responses of small, immature plants in a controlled chamber environment may not be a good predictor of effects on forest trees growing in situ (Karnosky et al, 2007b, Matyssek et al, 2007. This recognition of the importance of studying trees in the context of their normal environment is a step towards thinking about potential effects on the forest ecosystem as a whole and not just the major tree species that are the most obvious components.…”
Section: Ozone and Biogenic Vocsmentioning
confidence: 99%
“…Whereas the observed effects on Ponderosa pine and other conifers in California were associated with peak ozone concentrations that exceeded 200 nl l -1 (ppbv) (Miller and McBride, 1998), more recent studies have emphasised the overall increase in ozone concentrations outside major 'episodes', and the potential for chronic injury (Coyle et al, 2003). There have been successful experiments that have moved from the study of young trees (seedlings or saplings) in the laboratory to the field-scale fumigation of adult trees with ozone, recognising that the responses of small, immature plants in a controlled chamber environment may not be a good predictor of effects on forest trees growing in situ (Karnosky et al, 2007b, Matyssek et al, 2007. This recognition of the importance of studying trees in the context of their normal environment is a step towards thinking about potential effects on the forest ecosystem as a whole and not just the major tree species that are the most obvious components.…”
Section: Ozone and Biogenic Vocsmentioning
confidence: 99%
“…The forest grew on luvisol derived from loess over tertiary sediments with high nutrition and water supply. Long-term mean (1970Long-term mean ( -2000 annual air temperature and rainfall were 7.8 • C and 786 mm, respectively (monitored by Deutscher Wetterdienst at climate station "Weihenstephan", at 4 km distance from the research site; DWD Offenbach, Germany; Matyssek et al, 2007). Scaffoldings and a canopy crane provided access to the tree canopies.…”
Section: Experimental Designmentioning
confidence: 99%
“…Karnosky et al, 2001Karnosky et al, , 2007Nunn et al, 2002Nunn et al, , 2005Werner & Fabian 2002;Matyssek et al, 2007, 2010a, b andtherein reference). Free-air O 3 fumigation studies on field-grown trees have been conducted for several years at some locations in Europe and the US (Karnosky et al, 2001(Karnosky et al, , 2007Matyssek et al, 2007;Oksanen et al, 2007). All these studies have also shown that enhanced O 3 regimes have the capacity of counteracting the effects of elevated CO 2 and of substantial reduction of the carbon sink strength of woody-plant systems (Matyssek et al, 2010a, b).…”
Section: Introductionmentioning
confidence: 99%